PROTAGONISMO, EMPODERAMENTO E LIDERANÇA NA ENFERMAGEM: CONHECENDO A TRAJETÓRIA PROFISSIONAL DE ANNETTE KENNEDY - Anjos, Alyne Barbosa dos; Brandão, Amanda Andrade; Guedes, Bianca Lopes; Amorim, Carla Resende; Silva, Daianne Bragança da; Lana, Diana Debora Pereira de; Sousa, Luisa Paula De Almeida; Mansur, Odilson; Marques, Sabrina Pereira; Santos, Thales Augusto Sousa; et al. (Sinapse Múltipla, 2020)